Rekonstruksi Hukum Pemerintahan Daerah di Indonesia: Tantangan Globalisasi Terhadap Prinsip Otonomi dan Kedaulatan Nasional - I Wayan Suarsana; Cokorde Istri Dian Laksmi Dewi; Putu Eka Trisna Dewi (Jurnal Hukum Lex Generalis, 2025)
The changing global order and the growing interaction among nations demand a governance system capable of adapting to globalization dynamics without neglecting the principle of national sovereignty. In this context, examining regional government law becomes crucial to ensure that the implementation of regional autonomy remains consistent with Indonesia’s constitutional framework. This study aims to identify the role of regional autonomy in the governance system amid globalization. The research employs a normative juridical method with statutory and conceptual approaches. The data consist of secondary sources, including legislation, books, academic journals, and other relevant official documents. The results show that the implementation of regional government law aligns with Indonesia’s constitutional system in the globalization era. The manifestation of democratic and autonomy principles is evident through the decentralization of local governance, although the central government retains the main responsibility for regional administration. The novelty of this study lies in its comprehensive analysis of how globalization challenges Indonesia’s regional governance framework, emphasizing the need to strengthen regional government law to enhance independence, accountability, and public welfare. The findings imply that legal reform at the regional level is essential to balance local autonomy with national integration in facing global pressures.